Moral Salience, Situational Moral Evaluations, and Criminal Choice - Herman, Shaina (Crime & delinquency, 2025)
Research increasingly aims to better understand criminal behavior in context. Invariably, this entails integrating sociological (and other) perspectives on structure and environment, with psychological and economic notions of individual decision processes. Unique among environmental influences on crime is the immediate context surrounding an offending opportunity. Here we focus on moral context. Perceived choice is often constrained by structural factors, such as concentrated disadvantage and social inequalities, which restrict prosocial opportunities and encourage offending. System 1 heuristic processes that involve moral salience can affect perceived choice sets as well. Such processes narrow choices by directing attention to one or a subset of behavioral options and away from others. They can also expand choices by counteracting the attention narrowing, criminogenic influences of competing heuristics such as temporally present orientation. Below we examine whether contextual circumstances can amplify the internal prominence of one’s moral self-conception, thus influencing moral judgements and related action. Using randomized experiments embedded in two online surveys, we assess the role of morally laden situational cues in choice processes.